TAMS: development of a multipurpose three-arm aerial manipulator system. (2nd January 2021) - Paul, Hannibal; Miyazaki, Ryo; Ladig, Robert; Shimonomura, Kazuhiro
Abstract : This paper describes the concept, design and realization of a novel manipulator system for a multirotor aerial robot. The proposed manipulator system consists of three robotic arms attached to a multirotor frame. To overcome the limited payload capabilities in multirotor aerial platforms, the same set of on-board manipulators are used to realize various tasks, primarily the manipulation or grasping of objects of various sizes. Furthermore, they can provide aid in complex navigation tasks by doing physical, contact-based obstacle avoidance and are able to act as adaptive landing gear in uneven terrain. The design requirements and the analysis to realize these tasks is discussed. The proposal is supported with the successful demonstration of these tasks using the aerial multi manipulator system in an outdoor environment. GRAPHICAL ABSTRACT: UF0001